Preparation of pitch for melt-electrospinning from naphtha cracking bottom oil - Kim, J.; Lee, S.H.; Lee, Y.-S. (2013)
In this study, a pitch for melt-electrospinning was prepared from naphtha cracking bottom (NCB) oil by the modification with heat treatment. The softening point and property of the modified pitch was influenced by modification conditions such as nitrogen flow rate, heat treatment temperature, and reaction time. Among these, the heat treatment temperature had a very strong influence on the distribution of molecular weight and softening point of the pitch. The C/H mole ratio and average molecular weight increased with increasing the heat treatment temperature due the decomposition and cyclization reaction of surface-functional groups. In addition, the values of benzene insoluble and quinoline insoluble also tends to decrease, and the width of molecular weight distribution seems to get more narrow. The carbon fiber with a diameter of 4.8 μm was prepared from a modified pitch at the softening point of 155 °C by melt-electrospinning. It is believed that the melt-electro spinning method is much more convenient to get the thinner fiber than the conventional melt spinning method.